ANALISIS PERANAN SISTEM INFORMASI AKUNTANSI MANAJEMEN DAN SISTEM PENGENDALIAN MANAJEMEN DALAM MENINGKATKAN KINERJA PERUSAHAAN PADA PT. ASKRINDO CABANG SURABAYA - Oktavianty, Mufidah Sahla; Rachmawati, Titiek (Jurnal Ilmu Akuntansi, 2024)
The purpose of the study is the role of management accounting information systems and management control systems in improving company performance at PT Askrindo Surabaya Branch. In this research design, the goal is to analyze employee performance at PT Askrindo Surabaya branch with a focus on the Management Accounting Information System and Management Control System. This research uses descriptive methods with a qualitative approach, and primary data collected through observation, interviews and documentation. PT Askrindo Surabaya Branch which is located at Jalan Biliton No. 30, Gubeng, Kec. Gubeng, Surabaya City, East Java The results of this study are used to determine the role of SIAM characteristics consisting of “broadscope”, “timeliness”, “aggregation”, and “integration” have been applied in various aspects of company operations. Broadscope characteristics of internal and external information have been covered both from the head office and each division such as Finance&Accounting, HR & General, Claims & Subrogation, and Marketing. Timeliness characteristics in the form of reports to branch heads are carried out once a year, information is obtained and reported by each division on a weekly or monthly basis. Aggregation characteristics in the form of reports from each division are carried out periodically, either weekly, monthly, or annually.Integration: Each division makes records through their respective systems such as ACS, FMS, and AIR.  To store all the data that has been recorded into the system as well as measure the decisions taken, checking financial statements and services to credit customers.